Exploring academic hiring and life in humanities and social sciences at an English research university through a PhD students-as-partners project. (8th May 2017) - Brown, Katie; Mountford-Zimdars, Anna
Abstract : Purpose: The purpose of this study is twofold: to make explicit academics' tacit knowledge of academic employment and to develop the educational research and employability skills of 12 postgraduate researchers. Design/methodology/approach: Twelve postgraduate researchers from ten different disciplines conducted 24 semi-structured interviews (12 with early career academics, 12 with senior academics). Respondents shared the skills, experiences and attributes sought when hiring and their lived experience of being academics. Findings: The importance given to both explicitly stated (publications, teaching experience) and implicit (values, behaviour) factors varies greatly among individual academics. There is a mismatch between stated job requirements and the realities of academic life. A students-as-partners project fosters critical engagement with these questions and offers other benefits to participants. Research limitations/implications: Most respondents work at one research-intensive English institution, potentially limiting generalisability to teaching-led and international institutions. Practical/implications: Researcher development programmes should make explicit the range of factors considered in hiring while also encouraging critical engagement with the realities of academic work. Through students-as-partners projects, postgraduate research students can uncover first-hand what academic life is like and what hiring committees are looking for. Originality/value: Through involving students-as-partners, the research question changed to reflect the actual concerns of those contemplating an academic career. Students gained invaluable awareness of academic hiring and insights into academic life, as well as transferable skills.